2023
DOI: 10.1111/joop.12466
|View full text |Cite
|
Sign up to set email alerts
|

Daily strengths use and work performance: A self‐determination perspective

Hannah L. Moore,
Arnold B. Bakker,
Heleen van Mierlo
et al.

Abstract: Drawing on self‐determination theory, this study examines how using personal strengths at work in the morning is associated with different types of performance throughout the workday. Momentary satisfaction of the needs for autonomy, relatedness and competence are proposed as mechanisms that differentially link strengths use to four different performance outcomes: task accomplishment, goal attainment, organizational citizenship behaviour and counterproductive work behaviour. We collected data from 216 Dutch em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…Research has documented that strength-based interventions that focus on strength identification and use can lead to a wide scope of positive changes in one’s psychological, social, and occupational functioning, such as meaning pursuit, well-being, work performance, and education outcomes ( Ghielen et al, 2017 ; Quinlan et al, 2019 ; Dolev-Amit et al, 2021 ; Moore et al, 2024 ). Existing evidence has further shown that strength use, instead of strength identification, appears to be the active ingredient attributable for the observed positive changes in various domains (e.g., Govindjee and Linley, 2007 ; Wood et al, 2011 ; Littman-Ovadia et al, 2013 ; Miglianico et al, 2020 ).…”
Section: The Preventive Remedial and Developmental Mechanisms Under Pcpmentioning
confidence: 99%
“…Research has documented that strength-based interventions that focus on strength identification and use can lead to a wide scope of positive changes in one’s psychological, social, and occupational functioning, such as meaning pursuit, well-being, work performance, and education outcomes ( Ghielen et al, 2017 ; Quinlan et al, 2019 ; Dolev-Amit et al, 2021 ; Moore et al, 2024 ). Existing evidence has further shown that strength use, instead of strength identification, appears to be the active ingredient attributable for the observed positive changes in various domains (e.g., Govindjee and Linley, 2007 ; Wood et al, 2011 ; Littman-Ovadia et al, 2013 ; Miglianico et al, 2020 ).…”
Section: The Preventive Remedial and Developmental Mechanisms Under Pcpmentioning
confidence: 99%
“…This two-dimensional strengths use construct captures different but important forms of strengths use in organizations and allows us to investigate unique management phenomena within the Chinese cultural context. Grounded in strengths use theory, prior studies have provided initial evidence that SUT can fulfill employees' psychological needs, facilitate thriving at work and enhance their job performance (Moore et al, 2022(Moore et al, , 2023. SUR is positively associated with employees' well-being and work engagement, and is negatively related to turnover intention (Hai and Park, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Previous research on strengths use has predominantly focused on the role of strengths use in achieving task-related goals (Littman-Ovadia et al , 2017; Moore et al , 2023; van Woerkom et al , 2016a); however, knowledge on how employees use their strengths to realize relationship-related goals is surprisingly limited. Especially in the Chinese organizational context, which is influenced by Confucian culture, employees are not only required to perform work tasks well and meet the organization’s needs, but also to maintain harmonious relationships with others at work (Chen et al , 2015; Hu and Luo, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%